2006
DOI: 10.1007/bf03194648
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage in mouse lymphocytes exposed to curcumin and copper

Abstract: Dietary polyphenolics, such as curcumin, have shown antioxidant and anti-inflammatory effects. Some antioxidants cause DNA strand breaks in excess of transition metal ions, such as copper. The aim of this study was to evaluate the in vitro effect of curcumin in the presence of increasing concentrations of copper to induce DNA damage in murine leukocytes by the comet assay. Balb-C mouse lymphocytes were exposed to 50 microM curcumin and various concentrations of copper (10 microM, 100 microM and 200 microM). Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…The induction of DNA damage that we observed in HEp-2 and 7T cells following the treatment with curcumin is in agreement with those previously reported, despite differences in the type of cells and experimental conditions used (Cao et al, 2006;Huang et al, 2011;Jiang et al, 2010;Lin et al, 2008;Lopez-Lazaro et al, 2007;Su et al, 2006;Urbina-Cano et al, 2006). Although we have expected that more oxidative DNA damage (like oxidized purines) would appear in HEp-2 and 7T cells because of ROS induction, strand breaks were predominant and correlated with cytotoxicity.…”
Section: Discussionsupporting
confidence: 93%
“…The induction of DNA damage that we observed in HEp-2 and 7T cells following the treatment with curcumin is in agreement with those previously reported, despite differences in the type of cells and experimental conditions used (Cao et al, 2006;Huang et al, 2011;Jiang et al, 2010;Lin et al, 2008;Lopez-Lazaro et al, 2007;Su et al, 2006;Urbina-Cano et al, 2006). Although we have expected that more oxidative DNA damage (like oxidized purines) would appear in HEp-2 and 7T cells because of ROS induction, strand breaks were predominant and correlated with cytotoxicity.…”
Section: Discussionsupporting
confidence: 93%
“…Although the increase in ROS was transient, presumably because of a subsequent elevation in glutathione, cell viability was nevertheless decreased. Similarly, curcumin-mediated DNA damage was reported in mouse lymphocytes using a comet assay [222]. In contrast to these studies, Polasa et al [223] reported that curcumin inhibited B(a)P-induced strand breaks in human peripheral blood lymphocytes.…”
Section: Cautionary Talesmentioning
confidence: 85%
“…21 Accumulating data have demonstrated since then that curcumin can induce DNA damage and chromosomal alterations both in vitro and in vivo at concentrations similar to those reported to exert beneficial effect. [22][23][24][25][26][27][28][29][30] For instance, curcumin concentrations of 2.5 and 5 lg mL À1 were shown to induce DNA damage to both the mitochondrial and nuclear genomes in cells. 28 These reports raise concern about curcumin safety, as the induction of DNA alterations is a common event in carcinogenesis.…”
Section: Dear Editormentioning
confidence: 99%